Dampak Parking Stand Double Nose-In terhadap Pelayanan Lalu Lintas Udara di Perum LPPNPI Cabang Madya Denpasar - Irfan (Politeknik Penerbangan Makassar, 2019)
The objective of the research is to analyze the impact of double-parking stand nose-in order to improve the smoothness of aircraft movement. The method was performed through a qualitative descriptive data sourced from air traffic movement and unscheduled. The results showed that in the absence of double nose-in parking stand as well as the south apron used as a passenger terminal apron can load the entire amount of traffic arrival and departure. Thus, the parking stand at the north and south apron can be according to the standards that have a positive impact on the safety and smoothness of air traffic. It was therefore recommended that the north and south apron as the passenger terminal apron so that the regularity of air movement can be achieved.